DEFISIT NERVUS OLFAKTORIUS SEBAGAI FAKTOR RISIKO GANGGUAN MEMORI PADA LANSIA - Vincentius Henry Sundah,* Yuda Turana,*Yvonne Suzy Handajani* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION OLFACTORY DEFICIT BECOMES THE EARLY CLINICAL SIGN OF COGNITIVE FUNCTION IMPAIRMENT AMONG THE ELDERLY PEOPLE THIS RESEARCH FOCUSES ON SPECIFIC COGNITIVE FUNCTION IMPAIRMENT OF THE FRONTAL LOBE WHICH IS A REGION OF BRAIN THAT RESPONSIBLE WITH MANY FUNCTIONS INCLUDING OLFACTORY FUNCTION ATTENTION EXECUTIVE AND MEMORY COGNITIVE FUNCTION